Experience and social support needs of becoming a mother in adolescence in Yogyakarta City - Cut Oktaviyana; Intansari Nurjannah; Wenny Artanty Nisman (Berita Kedokteran Masyarakat (BKM), 2018)
PurposeThis study aimed to determine the experience and social support needs of becoming a mother in adolescence.MethodsThis study was a qualitative research with a descriptive phenomenology approach. Data collection was performed by in-depth interview method and using a semi-structured study guide. Research was conducted at health centers of Jetis, Gedong Tengen and Umbulharjo 1 in May - June 2017. The participants were 7 adolescent (18-19 years old) mothers who had a 2 weeks - 12 months baby. The sampling was conducted by purposive sampling and recorded by a tape recorder. Data analysis was done manually by using Colaizzi method.ResultsFive themes emerged from the results of data analysis: 1) variation of feelings experienced from pregnancy up to delivering the baby, 2) freedom from routine of baby care, 3) early experience of baby care, 4) social support from significant other and midwives, and 5) improved confidence in baby care.ConclusionThe variety of experiences by adolescent mothers is accompanied by social support providing increased confidence in caring for their baby.